Ameliorative properties of Iranian Trigonella foenum-graecum L. seeds and Punica granatum L. peel extracts in streptozotocin-induced experimental diabetic guinea pigs - Nabil Abdel Salam Ahmed Hasona; Mohammed Ahmed Qumani; Turki Ahmed Alghassab; Muath Abdulrahman Alghassab; Abdullah Ali Alghabban (Asian Pacific Journal of Tropical Biomedicine, 2017)
Objective: To assess the ameliorative properties of Iranian Trigonella foenum-graecum L. (T. foenum-graecum) seeds and Punica granatum L. (P. granatum) peel extracts against streptozotocin-induced diabetes in male guinea pigs. Methods: Sixty guinea pigs were divided into six groups (10 guinea pigs per group). Group 1 consisted of normal animals. Groups 2 and 3 were treated with Iranian T. foenum-graecum seeds and P. granatum peel extract alone, respectively. Group 4 was treated with streptozotocin only; whereas Groups 5 and 6 receiving streptozotocin were treated with Iranian T. foenum-graecum seeds and P. granatum peel extract, respectively. All animals were treated for 30 days, and the body weight, blood and liver biochemical parameters were measured. Results: Guinea pigs exposed to streptozotocin showed an alteration in body weight gain, fasting glucose level, kidney function parameters (blood urea nitrogen and creatinine) as well as decreased serum and hepatic total protein level. In addition, it increased the cholesterol and triglyceride level, while decreasing the hepatic glucose-6 phosphate dehydrogenase activity, glycogen, glutathione content and hepatic catalase activity. Oral treatment with T. foenum-graecum seeds and P. granatum peel extracts revealed significant protective properties with respect to body weight gain and other biochemical parameters studied. Conclusions: The Iranian T. foenum-graecum seeds and P. granatum peel extracts are significantly potent in ameliorating diabetic condition induced by streptozotocin and improving various biochemical parameters in serum and liver of guinea pigs.